Seroprevalence of hepatitis B infection and associated risk factors among drug users in drop-in centers of Isfahan, Iran - Roya Taleban (International Journal of Preventive Medicine, 2018)
Background: Scientists perceive drug users (DUs) as a high-risk population for hepatitis B virus (HBV) infection. Effective strategies aiming at the reduction of HBV infection can be depicted when its epidemiological status is clearly defined. The present study provides new insight into associated risk factors of HBV infection and its seroepidemiological status among DUs attending drop-in centers (DICs). Methods: This was a cross-sectional study, which was implemented in 7 DICs of Isfahan province. The sample size included 539 participants. Demographic data and risk factors for HBV infection were obtained by a trained social worker using a self-made structured questionnaire. Venous blood sample was obtained and tested for hepatitis B surface antigen (HBsAg), hepatitis B surface antibody, and total hepatitis B core antibody (HBcAb) using enzyme-linked immunosorbent assay. Results: Mean age of the participants was 31.76 ± 8.4 years. They were generally male, Iranian, urban, with an education level of high school or less. The prevalence of HBV infection (HBsAg and/or HBcAb) was 18% (88.490). Regression analysis showed that age, bloodletting, and drug injection, being the sexual partner of injecting DU (IDU), as well as frequency and duration of imprisonment positively correlated with HBV infection. Conclusions: Drug injection bloodletting, and being the sexual partner of IDU, as well as frequency and duration of imprisonment could be considered as contributing factors in HBV infection.